Sikap siswa terhadap penggunaan video podcast pada materi Larutan Penyangga - Fazita Apritama Dewi Fau; Nurfina Aznam (Postgraduate, University of Mataram, 2023)
The use of video podcasts has positively impacted student learning and engagement in various educational settings. In the specific case of learning about buffer solutions, video podcasts can effectively present key concepts and principles in an engaging and interactive way. This study aims to analyze students' attitudes toward the Video Podcast on Buffer Solution Material. The instrument used in this study is a closed-ended questionnaire consisting of 17 questions with six aspect categories: Overall, Explanation, Learning Features, Tempo, Interest, and Further Purpose. Then, 34 students from X MIPA at SMAN 1 Cangkringan were involved in this study. Total number of visitors for 5 days completed is 54 times. The students in this study had positive attitudes toward video podcast used to teach buffer solution concepts. It can be seen that the results of the student’s attitude towards podcast that overall students liked the podcast that was posted (80%). The result revealed that, in general, students liked the posted podcast, and the video helped them understand the buffer solution material. However, the effectiveness of video podcasts may depend on various factors, including the quality and relevance of the content, the integration of the podcasts into the overall teaching and learning process, and individual student needs and preferences. To ensure the best possible outcomes, teachers should carefully consider these factors when using video podcasts as a learning tool for buffer solution concepts.